Advertising Tax, Underground Water Tax, Swallow's Nest Tax during the Pandemic And the influence on ROI Cianjur Regency - Arosid, Deden Muhammad (Maksi, 2023)
The economic crisis that hit Indonesia due to the Covid-19 pandemic had a huge impact in several regions, one of which was Cianjur Regency. It is difficult for the government and the community to run the wheels of the economy, causing a decrease in local revenue. One of the sources of Regional Original Income (ROI) which has an important role is regional taxes. Based on previous studies, this research focused on 3 types of taxes, namely Advertising Tax, Underground Water Tax, and Swallow's Nest Tax. The purpose of this study was to find out how much influence these three taxes had on Cianjur Regency Regional Original Revenue during the Covid-19 pandemic. The method used in this research is descriptive method and verification method. The results showed that the Advertising Tax, Underground Water Tax, and Swallow's Nest Tax experienced an increase in tax revenue during the Covid-19 Pandemic and had an effect on the ROI of Cianjur Regency.